O nienaruszalność granic. Polsko-sowiecki spór polityczny o kształt wschodniej granicy Rzeczypospolitej po II wojnie światowej - Ostanek, Adam Adrian Ostanek (Przegląd Wschodnioeuropejski, 2023)
The Polish-Soviet conflict during World War II is one of the most complicated issues in legal terms. The war, which, although not declared, but visible in the form of military aggression, never took place in the eyes of the Soviet side. The course of the border and other international agreements, although signed without coercion in the international period, suddenly turned out to be worthless pieces of paper. The provisions of the Atlantic Charter, signed during the war and guaranteeing, inter alia, the inviolability of the borders, turned out not to apply to Poland. The aim of the article is to show what, in such a complicated situation, from the point of view of international law, the Polish-Soviet diplomatic dispute about the future of the Polish eastern border, which is also the border between the Republic of Poland and the Soviet Union, looked like. The source of the work are archival materials stored in British archives and scientific studies.